Kajian Literatur Pengembangan Pariwisata Bahari di Pulau Tunda, Banten dalam Tinjauan Ontologi, Epistimologi, dan Aksiologi - Dewi, Triana Rosalina; Tarigan, Emenina; Laksmi, Gratia Wirata; Nurbaeti, Nurbaeti; Rahmanita, Myrza (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2025)
This study aims to explore the potential for marine tourism development on Tunda Island by identifying the challenges faced, and providing sustainability-based solutions through ontology, epistemology, and axiology approaches. The research method used is an in-depth literature study, by analyzing various theories and concepts related to marine tourism development, and linking them to real conditions on Tunda Island. The main findings of this study indicate that marine tourism on Tunda Island faces major challenges in the form of environmental damage, limited infrastructure, and socio-economic inequality. The proposed solutions include strengthening the role of local communities in tourism management, implementing ecotourism, and integrating local and scientific knowledge into tourism destination management policies. The contribution of this study is to provide a more comprehensive understanding of the relationship between theory and practice in sustainable marine tourism development, and provide policy recommendations to ensure long-term benefits for local communities. In conclusion, marine tourism development on Tunda Island can run well if sustainability-based approaches and local community empowerment are implemented effectively, ensuring a balance between social, economic, and environmental aspects. Keywords: marine tourism, ontology, epistemology, axiology